Report on Intersex and Abnormal Mature Aquacultured Walleye Pollock, Gadus chalcogrammus - Hae-Kyun Yoo; Soo-Ji Woo; Ki-Wook Lee; Min-Soo Joo; Kyeong-Duck Kim; Jung-Jun Park; So-Sun Kim (Fishes)
Walleye pollock (Gadus chalcogrammus) is a commercially important species widely distributed in cold-water regions. We have been culturing this species artificially since 2015. The average embryo diameter was 1.43 ± 0.056 mm, and hatching occurred at 5 °C approximately 339 h post-fertilization. Gonadal development became visibly apparent at a body size of 10–15 cm after ~180 days, initially distinguishing ovaries with the development of germ cells, whereas testes were observable after further maturation. We discovered two intersexes from F1 and F2 generations, and one abnormal mature individual from F2. Morphologically, intersex walleye pollock exhibited distinct characteristics of ovary and testes, with male gonads visibly connected to the end of ovaries. In intersex walleye pollock aged 3–6 years, the gonads developed normally, and oocyte resorption was restricted to the area near the connections between testicular and ovarian tissues, with numerous atretic oocytes observed in the resorption zone. Primordial germ cells were found together in individuals who had not undergone spawning, indicating an abnormal maturation pattern. Although no significant differences in the gonadosomatic index were observed between intersex and normal individuals, further research on intersexuality is necessary to understand the reproductive development of this species and the health of offspring spawned by intersex individuals, which are rare.